Modification of Tergitol-7 Agar for Differentiation of Hydrogen Sulfide-Producing Colonies - Hinds, D. B. (1974)
The indication of H(2)S production by a modified Tergitol-7 agar combines the advantages of both selective and differential enteric media to provide a medium with broader coverage.